Wajah Baru Pendidikan Islam di Indonesia Masa Orde reformasi - Umar Umar (LPPM IAI Hasanuddin Pare-Kediri, 2015)
This article discusses how the new wajab of Islamic education at the time of the reform order, after decades of being in the government of the old order and the new order as if the government did not give opportunities for Islamic Education to take part freely. In writing this paper using literature review approach where data and data sources obtained from several libraries. The result is that the country needs an endless reformation, not a democratic euphoria, of all the elements of society, especially through education. Because with education all will be revitalized, education reform, especially Islamic education until now seems not to get serious attention, from the government itself, but there is no term late in doing something.